Vehicle or placebo? Investigators use incorrect terminology in randomized controlled trials half of the time: A systematic review of randomized controlled trials published in three major dermatology journals. - Shamsudin, Shamsudin; Fleischer, Alan B. (Strategic Communication in Dermatology, 2010)
Background: A topical comparison in a randomized controlled trial (RCT) should correctly be termed a vehicle rather than a placebo as the vehicle in a dermatologic drug product enhances delivery and efficacy of the active compound.